تقييم بعض أصناف اللوبيا ( Vigna unguiculata ( L.) Walp) من حيث النمو، وكمية الإنتاج، ونوعيته. - سمرة بديع; مخول سهيل; حسن هادية (Latakia University Journal -Biological Sciences Series, 2016)
this study was carried out during summer 2014 in Siano Research Station- the Agricultura Research Center in Lattakia . Four varieties of Cowpea: Dolicho (entrance), Blackey (entrance), Almaarefa (Local) and local cultivar were planted and compared concerning the vegetative growth , productivity and quality of green pods. The results showed the superiority of Almaarefa cultivar in some vegetative traits :plant hieght (166.66) cm compared with local cultivar 116.58 cm ,number of leaves on plant and( 27) leaves and( 17) leaves for local cultivar, and plant leaves area( 7840.23) cm2 for Almaarefa comparing with( 4499.75) cm2 for local cultivar As well as it had a maximum pod length( 16.71) cm and highest grain number of pod( 9.44) ,while Blackey cultivar was the most superior comparing with other cultivars in productivity( 0.6229) kg m 2 and pod’s number/m2 ( 81.069) Whereas Almaarefa had the lowest productivity( 0.4935) kg/m2 and lowest pod’s number ( 65.89)pod/m2. The results also showed that the local cultivar had the most vitamin C content comparing with other cultivars by( 23.765%) and in dry matter by (15.38%) , while there was no significant differences between protein green pods content. نفذ البحث في محطة بحوث سيانو التابعة لمركز البحوث العلمية الزراعية في اللاذقية خلال الموسم الزراعي 2014 . شملت الدراسة تقييم أربعة أصناف لوبياء هي : دوليكو (مدخل ) , وبلاكي (مدخل) , والمعرفة (محلي )، والصنف البلدي من حيث النمو الخضري , والإنتاجية، و الخصائص النوعية للقرون الخضراء. بينت نتائج الدراسة تفوق صنف المعرفة في ارتفاع النبات؛ إذ بلغ 166.66 سم مقارنة بالصنف المحلي 116.58سم , وفي عدد الأوراق على النبات 27ورقة للنبات مقابل 17ورقة للصنف المحلي، ومساحة المسطح الورقي 7840.23سم2مقارنة ب 4499.75 سم2 للصنف المحلي, كما تفوق هذا الصنف في طول القرن 16.71سم ,وعدد الحبوب فيه 9.44 حبة للقرن, بينما تفوق الصنف بلاكي على بقية الأصناف من حيث كمية الإنتاج 0.6229 كغ\م2، و عدد القرون 81.069قرن/ م2 ، و تميز صنف المعرفة بأقل كمية إنتاج 0.4935 كغ\م2, وأقل عدد قرون للنبات65.89 قرن/ م2 . وأظهرت النتائج أيضاً تفوق الصنف البلدي معنوياً على بقية الأصناف في محتوى قرونه الخضراء من فيتامينC ( 23.76% ) , وفي نسبة المادة الجافة (15.38% ) على بقية الأصناف المدروسة, بينما لم تكن الفروق معنوية في محتوى القرون الخضراء من البروتين .